Raising Awareness of Domestic Violence through the Application of Social Empathy to Game Design - Emery, Susannah Katharine Alice (Curtin University, 2021)
Consisting of a game prototype Hannah: A Friend in Need and an accompanying exegesis, this research explores the application of Segal’s (2006; 2011) social empathy theory to game design to strengthen support networks for victim-survivors of domestic violence (DV). Informed by academic research, narrative and game design elements inspired by Segal’s (2006; 2011) work were implemented in the narrative and interactive elements of the game to raise awareness of DV and promote empathy for victim-survivors.